The Influence of Recruitment, Placement, and Personnel Maintenance on the Work Performance of Police Members in the Gorontalo Regional Police - Paramata, Moh. Rolli; Suyanto, Moh. Afan; Usu, Idrus; Tuhala, Putri Baby Juliet (LPPPIPublishing, 2024)
This research was conducted with the aim of analyzing the Influence of Recruitment, Placement, and Personnel Maintenance on the Performance of Police Members in the Gorontalo Regional Police. This study is an associative research with a quantitative approach. Data analysis technique used multiple linear regression. Sampling was done by census involving the entire population as research samples. The results showed that partially recruitment has a positive and significant effect on the performance of police members in the Gorontalo Regional Police, placement has a positive and significant effect on the performance of police members in the Gorontalo Regional Police, personnel maintenance has a positive but not significant effect on the performance of police members in the Gorontalo Regional Police simultaneously recruitment, placement, and personnel maintenance have a positive and significant effect on the performance of police members in the Gorontalo Regional Police.